Multiband RF Circuits and Techniques for Wireless Transmitters - Chen, Wenhua; Rawat, Karun; Ghannouchi, Fadhel M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2016)
This book introduces systematic design methods for passive and active RF circuits and techniques, including state-of-the-art digital enhancement techniques. As the very first book dedicated to multiband RF circuits and techniques, this work provides an overview of the evolution of transmitter architecture and discusses current digital predistortion techniques. Readers will find a collection of novel research ideas and new architectures in concurrent multiband power dividers, power amplifiers and related digital enhancement techniques. This book will be of great interest to academic researchers, R&D engineers, wireless transmitter and protocol designers, as well as graduate students who wish to learn the core architectures, principles and methods of multiband RF circuits and techniques. .
RF Amplifier Design and Architectures -- Dual-Branch RF Amplifier Design and Architectures -- Multiband RF Transmitters -- Multiband RF Passive Circuits -- Multiband Power Amplifier Design -- Digital Techniques for Multiband RF Transmitters.
Keywords: Electronic circuits; Telecommunication; Electronic Circuits and Systems; Microwaves, RF Engineering and Optical Communications; Communications Engineering, Networks